Time-varying association between physical activity and risk of diabetes in the early and late adulthood: A longitudinal study in a West-Asian country. Issue 6 (December 2021) - Naseri, Parisa; Amiri, Parisa; Masihay-Akbar, Hasti; Vaighan, Navideh Sahebi; Ahmadizad, Sajad; Ghanbarian, Arash; Azizi, Fereidoun
Highlights: Assessment the possible changes in PA levels over time as a time-varying covariate. High physical activity can postpone the incidence of T2DM in middle- aged and elderly women. Sex and age groups are important factors in association between physical activity and risk of T2DM. Abstract: Background: The time-varying association between physical activity (PA) and incidence of type 2 diabetes (T2DM) is still unclear. The present study aimed to investigate this association in the early- and late-adulthood during a 9-year follow-up. Methods: This study was conducted on 3905 participants in early and late adulthood, using the Tehran Lipid and Glucose Study (TLGS) dataset. PA was assessed via the Iranian version of Modified Activity Questionnaire (MAQ). The association between trend of PA and incident T2DM was investigated using time-varying Cox's proportional hazard model. Variables including job, education, smoking and body mass index (BMI) were adjusted in the final model. Results: The distribution of sex- and age-specific levels of PA changed significantly over time. Compared with physically inactive women, for older women with high level of PA, the risk of T2DM was 0.64 (95% CI: 0.43−0.95, P = 0.02) in adjusted model. Moreover, hazard for low PA group was significantly higher than the moderate group, and for these two groups were significantly higher than high PA level (P < 0.05). Conclusion: High PA level can postpone the incident T2DM in early-aged and elderly women, over time. Therefore, gender and age are of great importance in designing the PA modifying programs to prevent T2DM.